2018
DOI: 10.1148/radiol.2018171593
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Intrahepatic Cholangiocarcinoma: Multiparametric MR Imaging to Predict Patient Survival

Abstract: Purpose To determine the performance of magnetic resonance (MR) imaging-based tumor metrics for evaluation of response to transarterial chemoembolization (TACE) in patients with unresectable intrahepatic cholangiocarcinoma (ICCA). Materials and Methods Ninety-four patients with unresectable ICCA underwent baseline and follow-up MR imaging after TACE and were followed up until death or end of study duration. Lesions were analyzed for anatomic (Response Evaluation Criteria in Solid Tumors [RECIST] and tumor volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…To determine this threshold, 10 tumors not part of our study cohort and confirmed to be completely necrotic at pathologic examination after liver transplant were assessed by using the above-described software and upper limit of venous enhancement parameter was determined to be used as threshold for viability. This has been described in a previous study (17). In summary, the voxel-wise enhancement…”
Section: Implications For Patient Caresupporting
confidence: 54%
See 2 more Smart Citations
“…To determine this threshold, 10 tumors not part of our study cohort and confirmed to be completely necrotic at pathologic examination after liver transplant were assessed by using the above-described software and upper limit of venous enhancement parameter was determined to be used as threshold for viability. This has been described in a previous study (17). In summary, the voxel-wise enhancement…”
Section: Implications For Patient Caresupporting
confidence: 54%
“…All patients were followed up until death or until December 2017. Ninety-four of the 111 patients have been previously reported on (17). This previous study evaluated the performance of MRI-based tumor metrics in evaluating response to TACE by comparing changes in baseline metrics to those obtained 1 month after TACE.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, prognostic predictions based on preoperative clinical and imaging information may benefit all patients with or without surgery and provide better guidance for individualized stratification for more patients. Predicting prognosis by imaging features is achievable because several studies have addressed the relationship between the imaging features of ICC and the tumor aggressiveness and patient outcome 2,27–30 . Our results showed that beyond the tumor number, other imaging features were correlated with patient outcome.…”
Section: Discussionmentioning
confidence: 62%
“…A standardized liver MRI protocol was performed in all patients enrolled using a 1.5T scanner (Magnetom Avanto, Siemens) with a phased array torso coil (repetition time ms/echo time ms, 5.77/2.77; eld of view 320-400 mm; matrix 192 x 160; slice thickness 2.5 mm; receiver bandwidth 64 kHz; ip angle 10 o ). The protocol included single-shot breath-held gradient-echo diffusion weighted echo-planar images, axial T2weighted fast spin-echo images, and unenhanced and contrast-enhanced (0.1 mmol/kg intravenous gadopentetate; Magnevist; Bayer) breath-held axial T1-weighted 3D fat-suppressed spoiled gradient-echo images in the hepatic arterial, portal venous and delayed phases (20s, 70s, and 180s, respectively) 24,32,33 .…”
Section: Imaging Protocolmentioning
confidence: 99%